Liquidity creation without a lender of last resort: Clearinghouse loan certificates in the banking panic of 1907 - Ellis W. Tallman; Jon R. Moen (Federal Reserve Bank of Atlanta, 2007)
We employ a new data set comprised of disaggregate figures on clearinghouse loan certificate issues in New York City to document how the dominant national banks were crucial providers of temporary liquidity during the Panic of 1907. Clearinghouse loan certificates were essentially bridge loans arranged between clearinghouse members that enabled and were issued in anticipation of monetary gold imports, which took a few weeks to arrive. The large New York City national banks acted as private liquidity providers by requesting (and the New York clearinghouse issuing) a volume of clearinghouse loan certificates beyond their own immediate liquidity needs. While loan certificates were a temporary solution at best to the liquidity crisis in 1907, their issuance allowed the New York banks to serve their role as central reserve city banks in the national banking system.
Keywords: N11; N21; E42; D71; 330; clearinghouse; financial crisis; panic; lender of last resort